IMPLEMENTASI PROGRAM PENCATATAN AKTA KEMATIAN DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL - Nindya Alvina K.; Dyah Lituhayu (Journal of Public Policy and Management Review, 2017)
Based on the Act No. 24 of 2013, Population Administration is a series of structuring and controlling activities in publishing Document and Population Data through Population Registration, Civil Registration, Population Administration Information Management and the empowerment of the result for public service and the development of other sectors.In this population administration, there are several population administration structuring programs. One of the programs is the death certificate. This study aimed to see the performance of death certificate registration program as well as explain how the regulation runs and the obstacle encountered in the implementation process of death certificate registration program in the Department of Population and Civil Registration Semarang.The analysis techniques used to obtain the data were interview, observation, and supporting documents. The theory used in this study was a theory from Merilee S. Grindle. The theory has two variables in carrying out the policy implementation, namely policy content and policy environment. Based on the two variables, it was taken three indicators which were used to assess the implementation of the program, namely the performance level,the change degree, as well as the compliance and responsiveness. Socialization The result of the study indicates that the performance level of death certificate registration program in Semarang is still low compared to the other programs, amounted to 20,60 %. Other obstacles found in the implementation were socialization effort which was not maximum, inadequate resources, a low level of compliance, as well as the miss communication from the implementers of the policy. Recommendations that can be given are improving the quality of resources, maximizing the efforts to improve performance, doing direct review, cooperating with relevant parties, and improving physical quality that is already available.